Global Health Law - Lawrence O. Gostin (Harvard University Press, 2014)
This is a unique moment to offer a systematic account of global health law. The promise of potential solutions to improve life prospects for the world’s population has captured the imagination of a new generation of philanthropists, scientists, celebrities, entrepreneurs, students, and citizens eager to make a difference in our interconnected planet. International development assistance for health— a crucial aspect of foreign policy— has qua dru pled over the past two de cades, from $5.6 billion in 1990 to $26.9 billion in 2010, with the private and voluntary sectors taking on an ever- increasing share of the total. Given the rapid and expanding globalization that is a defi ning feature of today’s world, the need for a robust system of global health law has never been greater. Throughout this volume, I stress the important diplomatic, po liti cal, social, and economic factors that give scope, substance, and structure to global health law. The policy objectives that make global health law so vital and vibrant range from the imperative of safeguarding the population’s health to national security, economic prosperity, and sustainable development, through to normative commitments to human rights and social justice. My goals in writing this book are to (1) defi ne the fi eld of global health law within the broader currents of global governance for health; (2) systematically describe and analyze the major sources of law, together with their institutional frameworks; and (3) develop critical themes that ought to guide global health in the twenty- fi rst century.